Effectiveness, treatment durability, and treatment costs of canagliflozin and glucagon-like peptide-1 receptor agonists in patients with type 2 diabetes in the USA - Mukul Singhal; Hiangkiat Tan; Craig I Coleman; Michelle Han; Chi Nguyen; Michael Ingham (BMJ Open Diabetes Research & Care)
Introduction This real-world study compared glycemic effectiveness, treatment durability, and treatment costs with canagliflozin 300 mg versus any dose of glucagon-like peptide-1 (GLP-1) receptor agonists in patients with type 2 diabetes mellitus (T2DM) in the USA.Research design and methods A retrospective cohort study using administrative claims and laboratory data (1 April 2012 to 28 February 2017) from the HealthCore Integrated Research Database were used to assess mean HbA1c at 3-month intervals, achievement of HbA1c thresholds (<7.0%, <8.0%, <9.0%), and treatment durability (ie, adherence, discontinuation, switching, treatment failure (ie, exceeding threshold (7.0%, 8.0%, 9.0%), having a prescription for a new antihyperglycemic agent)) in adults with T2DM who initiated canagliflozin 300 mg or any dose of a GLP-1 receptor agonist. Medication costs were calculated for adherent patients.Results There were no significant differences in the primary outcome of HbA1c levels at 3-month intervals (≤12 months) in the canagliflozin 300 mg versus any dose GLP-1 receptor agonist cohort. The likelihood of achieving HbA1c<8.0% was not different (p=0.666), the likelihood of achieving HbA1c<7.0% was lower (p=0.016), and the likelihood of achieving HbA1c<9.0% was higher (p=0.020) in the canagliflozin 300 mg versus any dose GLP-1 receptor agonist cohort. The likelihood of treatment failure after reaching any HbA1c target was not different between cohorts. A higher proportion of patients were adherent to treatment (p<0.0001) and a lower proportion discontinued (p<0.0001) or switched medication (p=0.023) in the canagliflozin 300 mg versus any dose GLP-1 receptor agonist cohort. Over 1 year, medication costs were $1421 (p<0.001) lower with canagliflozin 300 mg than any dose of GLP-1 receptor agonists.Conclusions This real-world, US-based study found that initiation of canagliflozin 300 mg versus any dose of a GLP-1 receptor agonist in patients with T2DM was not associated with significant differences in the primary outcome of HbA1c levels at 3-month intervals for up to 12 months after index, but showed better adherence, less discontinuation, and lower drug acquisition costs compared with initiation of any dose of a GLP-1 receptor agonist.